Bibliometric Mapping of Research on Mathematical Representation Ability in Indonesia (2020–2025) - Risya Qodaria; Rohati Rohati; Marlina Marlina (Journal of General Education and Humanities, 2025)
This study analyses publication trends in the study of mathematical representation ability in Indonesia using a bibliometric approach. A total of 71 articles published between 2016 and 2025 were analysed, with a focus on the period from 2020 to 2025. Data were collected from Publish or Perish, SINTA, Open Knowledge, and Scopus, and then analysed both quantitatively and descriptively based on the year of publication, journal indexation, research method, citation, and keywords. The results indicate that publications reached a peak in 2022 and then declined from 2023 to 2025. Of all the articles analysed, 77% were published in national journals, while international publications were still very limited. Furthermore, the dominance of qualitative methods is 62%, followed by quasi-experimental and quantitative methods. Keyword analysis revealed a major cluster of "mathematical representation abilities" that are heavily associated with student characteristics and learning strategies. This study offers a comprehensive overview of the development of mathematical representation research in Indonesia, highlighting the need to expand scientific collaboration and enhance representation competence in future education policies.